PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Badan Usaha Milik Negara Nonkeuangan yang Terdaftar pada BEI Tahun 2019-2023) - Mutiara Tsari Trinanda Dalimunthe; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of financial performance, capital structure, and corporate governance mechanism on firm value. The variables used in the analysis are profitability, liquidity, capital structure, institutional ownership, and firm value as the dependent variable. The study focuses on non-financial state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the period 2019–2023, with a total of 78 samples.The sample selection was based on purposive sampling using specific criteria. Multiple linear regression analysis was employed as the analytical method in this study. The results indicate that profitability and institutional ownership have a significant positive relationship with firm value, while, liquidity has a significant negative effect on firm value. This study also finds that capital structure has no effect on firm value.